780 Are E-Scooters Safe for Widespread Public Use? A Case Series Examining Severe Facial Injuries Secondary to E-Scooter Accidents. (19th August 2022) - Noton, T; Armes, H; Mistry, R; Tam, A; Collier, J; Greaney, L
Abstract: E-scooter use is becoming commonplace across the UK as an increasing number of towns and cities launch trials with pay-as-you-go e-scooter companies. In addition, e-scooters are cheap method of transport, easily available for an individual to purchase online, without restriction. We present two cases of patients having suffered complex facial injuries secondary to e-scooter accidents. The first is a 38-year-old male, who was thrown from an e-scooter and had associated loss of consciousness. CT facial bones demonstrated extensive fractures to the bilateral maxillary and frontal sinuses, nasal bones, bilateral orbital floors, and mandible. The Le Fort II and mandibular fractures were fixed in two procedures. The patient has ongoing neuropathic pain around the right mandibular condyle and is receiving input from orthognathic specialists. The second patient is a 60-year-old male, who collided with the rear of a car and was thrown forward, hitting his face on the tarmac. CT facial bones showed a Le Fort II fracture pattern and a fractured left inferior orbital rim, with extensive surgical emphysema of the face. He underwent plating of the bilateral Le Fort II fractures and application of intermaxillary fixation wires. With little to no enforcement of personal protective equipment use and safety advice whilst utilising e-scooter services, the number of people suffering serious injuries from using such equipment is set to skyrocket. Increased awareness and education around the danger of e-scooters needs to be addressed and should be prioritised by local authorities and public health services.